Molecular Systematics of Valerianella Mill. (Caprifoliaceae): Challenging the Taxonomic Value of Genetically Controlled Carpological Traits - Itziar Arnelas; Ernesto Pérez-Collazos; Josefa López-Martínez; Juan Antonio Devesa; Pilar Catalán (Plants, 2022)
Valerianella (cornsalad) is a taxonomically complex genus formed by 50–65 annual Holarctic species classified into at least four main sections. Carpological traits (sizes and shapes of achenes and calyx teeth) have been used to characterize its sections and species. However, the potential systematic value of these traits at different taxonomic ranks (from sections to species (and infraspecific taxa)) has not been tested phylogenetically yet. Here, we have assessed the evolutionary systematic value of Valerianella diagnostic carpological traits at different hierarchical ranks and have demonstrated their ability to separate taxa at the sectional level but not at species level for species of several species pairs. A total of 426 individuals (17 species, 4 sections) of Valerianella were analyzed using AFLP and plastid data. Genetic clusters, phylogenetic trees, and haplotype networks support the taxonomic classification of Valerianella at the four studied sectional levels (V. sects. Valerianella, Cornigerae, Coronatae, Platycoelae) but show admixture for ten taxa from five species pairs (V. locusta—V. carinata, V. coronata—V. pumila, V. multidentata—V. discoidea, V. dentata—V. rimosa, V. eriocarpa—V. microcarpa), which are not reciprocally monophyletic. Dating analyses indicate that the Valerianella sections are relatively old (mid-Miocene), while most species diverged in the Pliocene–Pleistocene. A new section Valerianella sect. Stipitae is described to accommodate the highly divergent and taxonomically distinct V. fusiformis type species. Taxonomic treatments that recognize the sectional ranks and that subsume the separate species of each species pair into single species represent a natural classification for Valerianella.